Jenis-jenis Capung (Odonata) di Kawasan Taman Satwa Kandi Kota Sawahlunto, Sumatera Barat - Silvy Olivia Hanum; Siti Salmah; - Dahelmi (Jurnal Biologi Universitas Andalas, 2013)
The study on dragonfly (Odonata) had been conducted in Kandi Wildlife Park Area, Sawahlunto City, West Sumatra. This study used descriptive method and survey in which dragonflies were collected directly by using insect net. In this study, 15 species of dragonfly were recorded, they were consist of 14 genera with four families, Gomphidae with two species and two genera, Libellulidae with 11 species and nine genera, Calopterygidae with one species and one genus and Protoneuridae with two species and two genus. Microhabitats of each species where discussed in relation to environment.Keywords: Insect, dragonflies, species, wildlife park